Cultural factors in the development of international projects: a case study of South Africa and Germany in the engineering/construction industry - Jogessar, Yashmee Bhana (My University, 2018)
The research was conducted to investigate the existing cultural factors that influence international projects and whether project teams are aware of these dynamics. The research specifically focused on South African and German project teams. One company from each country was chosen for the investigation; namely Company SA (from South Africa) and Company GER (from Germany); Company SA is Company GER’s subsidiary company. The project teams that were included for data collection were working on the Medupi/Kusile coal-fired, new-build power stations. The commissioning of these power stations is severely delayed. A case study approach was utilised to collect data; and qualitative methods were incorporated. This entailed conducting semi-structured interviews with six managers; two of which were based at Company SA and four at Company GER, respectively; and participant observations at Company SA’s and Company GER’s prefabrication workshops. Cultural factors do exist in international projects and the project-specific ones were summarised for the project relationship between the South Africans and Germans. Furthermore, the management level is mindful of cultural factors; however, their employees are not consciously aware that the reasons for their differences stem from cultural diversities. All managers also were of the opinion that management of cultural factors do affect the successful outcome of projects. Both companies have not provided their employees with a fixed technique or process on how to manage and adapt in projects with variable cultures. Some recommendations were included regarding methods to increase knowledge and manage an international project where there is cultural diversity; including specifics to manage a South African and German project.
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering (Mechanical, Industrial, and Aeronautical Engineering), October 2017
Keywords: International business enterprises--Management--Social aspects; Project management--Case studies; Industrial management--Cross-cultural studies; Intercultural communication; Corporate culture; Joint ventures